Preservice teachers’ evaluation of evidential support in causal arguments about educational topics - Lederer, Andreas; Thomm, Eva; Bauer, Johannes (Frontiers in Education, 2024)
Many questions about educational topics – such as the effectiveness of teaching methods – are of causal nature. Yet, reasoning about causality is prone to widespread fallacies, such as mistaking correlation for causation. This study examined preservice teachers’ ability to evaluate how various types of evidence provide adequate support for causal claims, using psychology students as a comparison group. The experiment followed a 2 x 3 mixed design with the within-participant factor evidence type (i.e., anecdotal, correlational, experimental) and the between-participants factor study field (i.e., teacher education, psychology). Participants (N = 135) sequentially read short texts on three different educational topics, each presenting a claim and associated evidence. For each topic, participants indicated their claim agreement, and evaluated the convincingness of the argument and the strength of the evidential support. Results from mixed ANOVAs displayed main effects for evidence type on the convincingness of the argument and strength of evidential support, but not on individual claim agreement. Participants found experimental evidence to be more convincing and to provide stronger support for causal claims compared to anecdotal evidence. This pattern occurred similarly for both student groups and remained stable when controlling for cognitive and motivational covariates. Overall, preservice teachers seem to possess a basic understanding of different kinds of evidence and their differential strength in supporting causal arguments. Teacher education may build upon this foundational knowledge to enhance future teachers’ competencies in critically appraising evidence from educational research and relating it to school-related claims and issues.